(untitled) (Research, Society and Development, 2021)
The research dealt with is a case study to know the possible environmental impacts by replacing fluorescent lamps with LED lamps in the University Hospital of the Food and Nutrition Unit Onofre Lopes, from the comparative dimensions of the types of lamps. To start the data collection was made a visit to feed unit, where in each sector was done counting lamps was working and the area measured in square meters. Before the results, it was noticed that the disadvantage of LED compared to CFLs is low lumen output, which is about half the luminous flux emitted by fluorescent lamps normally. The advantages of LED lamps is their low environmental impact and long service life. But for this to happen should be established minimum requirements for the quality of LED lighting. For despite the fact that the best products meet the human visual needs, this is not observed in the market as a whole. Thus, it could be concluded that the luminous efficiencies presented by the LEDs are close to those found in compact fluorescent bulbs. The substitution of one product for another, makes it necessary to analyze each case. You can find LED efficiencies below the mean values for compact fluorescent, which does not allow the affirmation that the LED is necessarily always more efficient.